Versatility of biodegradable temporizing matrix in acute burn management: Invasive procedures through a synthetic dermal substitute - Joanneke Maitz; Therese Pham; Daniel Isacson; Rodney Martin; James Laycock; Matthew Rickard; Peter Maitz (Burns Open)
Large, severe burn injuries are an acute and traumatic injury that require complex treatment and management strategies. NovoSorb Biodegradable Temporizing Matrix (BTM) is a synthetic dermal template that has been proven effective in the management of large burns to temporize wounds and improve functional and aesthetic outcomes. In large, severe burns, vascular access and other invasive procedures for tube, drain or cannula placement are integral to the management. Traditionally, these procedures are performed through native skin, avoiding transection through wounds. However, in large severe burn injuries finding an area of unburnt and viable skin is challenging. In this case, we report the successful insertion of intravenous cannulation, an end-ileostomy, and a tracheostomy through BTM in a 23-year-old male with 95% total body surface area (TBSA) burns. Challenges and learning points were met with simple and cost-effective solutions. This case highlights the versatility of BTM, suggesting that once partially or fully integrated, the neo-dermis can be treated like native skin for invasive procedures or surgical interventions. This is the first documented case of tracheostomy and ileostomy through BTM, providing valuable insights into its application in acute and traumatic burn injuries and large surface area wounds.